Tradisi Kalei Bunti Dalam Perspektif Pendidikan Agama Islam: Studi pada Masyarakat Desa Bolo Madapangga - Ismi Nurkhairani; Samsudin Samsudin; Junaidin Junaidin (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the existence of the Kalei Bunti tradition and identify the Islamic educational values embedded within it among the community of Bolo Village, Madapangga Subdistrict, Bima Regency. This study employs a qualitative approach with an ethnographic design. Data were collected through in-depth interviews, observation, and documentation, involving religious leaders, traditional leaders, community leaders, and residents who directly participate in the practice of this tradition. The research findings indicate that the Kalei Bunti tradition is still upheld by the community because it is viewed as a cultural heritage from their ancestors, a means of strengthening social integration, and is accepted from a religious perspective as long as its practice does not conflict with the principles of Islamic sharia. This tradition also embodies a number of Islamic educational values, including: (1) the values of ukhuwah and ta‘awun—or the spirit of brotherhood and mutual aid; (2) the value of gratitude to Allah the Almighty; (3) the values of good character and politeness; and (4) the value of respect for parents and elders as an expression of birrul walidain. Nevertheless, certain elements of this tradition still need to be critically examined, particularly those that have the potential to lead to wastefulness and those related to beliefs in specific symbols. In this context, Islamic religious education plays a vital role in fostering understanding and ensuring that the practice of these traditions remains consistent with the principles of Sharia. With proper management, the Kalei Bunti tradition has the potential to be developed as an effective non-formal educational medium for instilling moral, social, and spiritual values rooted in local culture. The selective and educational preservation of this tradition can be utilized as a means of fostering Islamic character that remains relevant to the development of modern society, while simultaneously strengthening the Islamic identity of the Bima community.